THE GREEK ANTI-PARADIGM: HOW LEGISLATION ON AGRICULTURAL CO-OPERATIVES CAUSED THEIR FAILURE - Fefes, Michael (International Journal of Cooperative Law, 2025)
The first piece of Greek co-operative legislation was promulgated in 1914. This legal regime remained till 1979,having been amended several times. Since 1979, there were seven laws concerning exclusively rural co-operatives. One may presume that such interest shown by Greek legislators would mean the development and expansion of co-operative model in rural sector. Nevertheless,theco-operative enterprise model has been a failure in Greece, at least as regards rural co-operatives. The present paper attemptsto point out that Greek legislation has played a negative role forruralco-operatives and had a serious contribution to their decline instead of serving as an encouraging and enforcing factor to their routing and betterment. In addition, one may stipulate that Greek legislation follows a specific pattern with the purpose to supervise and control rural co-operatives, treating themnot as enterprises but as political tools. The above comments will be based on theanalysis of three relevant laws in Greece, that is Law 1541/1985, Law 4015/2011 and Law 4384/2016, while a very brief commendation is to be done as to the very recent development on 11thMarch 2020 (Law 4673/2020).